2013 Global chemical industry mergers and acquisitions outlook (New York, 2013)
"The global chemical industry continues to face a number of trends that will challenge the sector and drive new opportunities for organic and inorganic growth. New markets, shale gas discoveries, and Advanced Materials Systems are among the trends driving organic growth and stimulating activity in mergers and acquisitions (M&A) and alliances. The industry is witnessing portfolio realignment as companies take steps to strengthen balance sheets, pursue consolidation strategies, and establish footholds in new markets. Although recent M&A activity levels have been lower than the levels seen in 2007 and 2008, significant M&A activity is still underway and an important element of today’s chemical industry."